Challenges of retaining senior managers at the Department of Social Development - Malafahlo, Constance Boni (My University, 2015)
This study explored challenges of retaining senior managers at the department of social development focusing on the Comprehensive Social Security branch. A comprehensive study of the literature was conducted and numerous themes pertaining to retention were identified. These themes were central to shedding light on key issues apposite to employee retention; and assisted in setting the broad context of what the study would be articulating. The themes identified in the literature were: employee retention, employee turnover, exit interviews, job satisfaction and staff morale. A basic qualitative research method was adopted in order to understand how DSD senior managers make sense of their work experiences. An interview guide was developed to gather the participant’s feelings, beliefs and perceptions around the topic of retention. The data collected from the interviews was subjected to thematic analysis in order to identify patterns of meaning across the dataset. The themes that emerged from the coded process of analysis were: organisational red tape, performance appraisal, better opportunities, organisational climate and employee morale. These themes were identified as the underlying factors to the inefficient and ineffective management of retention in the department. The results of the study have assisted to reflect on factors that could lead to turnover while identifying and affirming the challenges faced by the department in retaining their senior managers. The conclusions thereof culminated in recommending ways of mitigating the scourge; which will be valuable to the department to enhance performance by retaining their high performing senior managers. The recommendations were following through from the themes and conclusions, paying attention to each one of them as follows: Cut the red tape; appraise efficiently; be the best opportunity; survey the climate; and boost employee morale Even though the study may not lead to generalizations of conclusions drawn, it will contribute to the employee retention literature and serve as a basis for future studies.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2015.